IoT Smart Gardening on Herbal Plant and Analytic Virtualization Platform System - Abdul Ghafar, Nor Iskandar; Kassim, Murizah (Society of Visual Informatics, 2024)
The Internet of Things (IoT) is an emerging technology developing recently. The technology of IoT allows users to communicate with controllers and sensors, which are widely used in the agricultural sector, such as farming and weather forecasts. Recently, it has been identified that traditional herbal home gardens are difficult to monitor where herbal plants are sensitive and need a proper monitor. This research has developed an IoT smart gardening for herbal plant systems that helps to analyze four herbal plant types: Aloe Barbadensis miller, Salvia Rosmarimus, Clinacanthus nutans, and Curcuma. The system was designed using a NodeMCU ESP32 controller, soil moisture sensor, and DHT11 temperature and humidity sensor. The collected data was monitored in real-time on the Blynk platform via mobile phones and web browsers on sunny and rainy days. The result shows that the highest temperature on a sunny day was captured at 30°C, and the lowest was 26°C. However, during a rainy day, the highest temperature captured is 28°C and the lowest was 24°C. The highest humidity percentage on a sunny day was 80%, and the lowest was 40%, while the highest humidity on a rainy day was 98%, and the lowest was 68%. The soil moisture data that captured the water content of the soil of each herbal plant on a sunny day has been lost due to high temperatures. However, each herbal plant barely lost its water content due to low temperature and high humidity percentage conditions. The comparison showed that temperature, humidity, and weather could affect the water content in the soil. This research has significantly improved the agriculture sector in monitoring herbal plants and moving from traditional planting with an IoT system concept.